Analysis of influencing factors of shear wave elastography of the superficial tissue: A phantom study - Chen, Qiyang; Shi, Baixue; Zheng, Yang; Hu, Xiangdong (Frontiers in Medicine, 2022)
Shear wave elastography (SWE) is widely used in clinical work. But there is no standard protocol and operation specification for SWE acquisition methods, which impacts the diagnosis and clinical staging. This study aimed to investigate the influence factors of diameter, depth, and stiffness on SWE using different probes at superficial depths and discuss SWE differences with two machines at superficial depths. We performed SWE on two elastic phantoms that each phantom contained 6 subjects with two stiffness (41.06 ± 4.62 kpa and 57.30 ± 4.31 kpa), three diameters (10 mm, 15 mm, and 18 mm), and two depths (15mm and 25mm). A total of 240 measurements were obtained by using two ultrasound machines (SuperSonic Imagine Aixplorer and Mindray Resona 7) and 4 probes (SL15-4 and SL10-2, L11-3, and L14-5). The measurements were compared among 4 probes, 3 diameters, and 2 depths. There was no significant difference in SWE measurements among the probes from the same machine. The SWE measurements were affected by diameter, and the degree of influence was related to the stiffness. The SWE measurements were unaffected at a 15 mm to 25 mm depth range.